2005
DOI: 10.1111/j.1365-2672.2004.02453.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutation method for increased cellulase production

Abstract: This new method could be applied to obtain potent fungal mutants for more enzymes production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(72 citation statements)
references
References 24 publications
(19 reference statements)
0
64
0
2
Order By: Relevance
“…Furthermore, Dhawan et al (2003) reported that growing fungus Cyathus bulleri mutated by phenanthridine dye ethidium bromide could produce a 4.2-fold increase in laccase production as compared to the untreated fungus. Our results, combined with those of others including Chand et al (2005) and Dhawan et al (2003), have shown that the fungal spores or mycelia grown with mutagens can be an effective method for enhancing the objective products' production.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Furthermore, Dhawan et al (2003) reported that growing fungus Cyathus bulleri mutated by phenanthridine dye ethidium bromide could produce a 4.2-fold increase in laccase production as compared to the untreated fungus. Our results, combined with those of others including Chand et al (2005) and Dhawan et al (2003), have shown that the fungal spores or mycelia grown with mutagens can be an effective method for enhancing the objective products' production.…”
Section: Discussionmentioning
confidence: 77%
“…However, some reports showed that subjecting the dormant spores to microwave or ultraviolet light irradiation could not obtain obvious results (Anwar et al 1996;Xia et al 2007). While Chand et al (2005) reported that germinating spores of Aspergillus and Trichoderma species treated with ethidium bromide and ultraviolet light were effective methods for improving cellulase production. Furthermore, Dhawan et al (2003) reported that growing fungus Cyathus bulleri mutated by phenanthridine dye ethidium bromide could produce a 4.2-fold increase in laccase production as compared to the untreated fungus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang et al (2011) observed CMCase activity in T. viride mutants reaching 18 U ml -1 , which was also three times higher than in the wild type strain. Chand et al (2005) measured about 0.415 and 0.60 U ml -1 in endoglucanase activity in Aspergillus mutants compared to 0.280 U ml -1 in the wild type strain. Another study tested Penicillium echinulatum using various cellulosic substrates and detected the maximum CMCase activity as 1.53 U ml -1 (Martins et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Many traditional mutagenic strategies have been used to improve this characteristic, nevertheless, these attempts have not been totally successful yet (Chand et al, 2005;Kovàcz et al, 2008;Kovàcz et al, 2009;Jiang et al, 2011), since current enzyme production involves high costs and the production process is not yet fully defined (Adsul et al, 2007).…”
Section: Introductionmentioning
confidence: 99%